On some directions in improvement of state regulation of marketing products of hunting industry - I. A. Grebnev; A. V. Pushkin; A. V. Blinova (Аграрная наука Евро-Северо-Востока, 2017)
It is possible to ensure the country's food security within hunting industry mostly by means of developing the market of food products of hunting industry as well as by increasing self-sustainment and self-employment of rural hunters. In order to improve the quality of nutrition it is important to obtain the diet containing foods of natural origin, which are rarely or never used. At present, state regulation of marketing products of hunting industry has a number of excessive administrative barriers at various stages of production and marketing. At the stage of production (harvesting game resources) there are excessive limitations on permissible tools and methods used. Therefore, we propose to introduce some changes in the existing legislation by repealing the ban on snaring hazel-grouse. At the stage of marketing products of hunting industry there are a number of administrative barriers associated with the rules of veterinary examination of slaughter animals and the rules of veterinary and sanitary expertise of meat and meat products and their marketing. It would be advisable to repeal the regulation on the necessity to get a veterinary certificate №2 for wildfowl to be sold outside an administrative district. Furthermore, it is necessary to repeal a discriminative regulation according to which individual amateur hunters have to sell their game harvest if it is not used for personal consumption - to enterprises specializing in purchasing products of hunting industry.